2023
DOI: 10.1001/jamanetworkopen.2023.25914
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers Associated With Severe COVID-19 Among Populations With High Cardiometabolic Risk

Abstract: ImportanceCardiometabolic parameters are established risk factors for COVID-19 severity. The identification of causal or protective biomarkers for COVID-19 severity may facilitate the development of novel therapies.ObjectiveTo identify protein biomarkers that promote or reduce COVID-19 severity and that mediate the association of cardiometabolic risk factors with COVID-19 severity.Design, Setting, and ParticipantsThis genetic association study using 2-sample mendelian randomization (MR) was conducted in 2022 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Additionally, another review and meta-analysis conducted in the first year of the pandemic showed that obesity increased the risk of hospitalization and mortality among COVID-19 patients [ 14 ]. Furthermore, an international genetic study that included over 200,000 subjects found that diabetes was one of the factors that increased the risk of COVID-19-related death [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, another review and meta-analysis conducted in the first year of the pandemic showed that obesity increased the risk of hospitalization and mortality among COVID-19 patients [ 14 ]. Furthermore, an international genetic study that included over 200,000 subjects found that diabetes was one of the factors that increased the risk of COVID-19-related death [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that even short-term exposure to air pollution increases the susceptibility to SARS-CoV-2 infection [ 6 , 7 ]. More recently, a genetic association study that employed the mendelian randomization to explore the relationship between cardiometabolic risk biomarkers and severe SARS-CoV-2 infection has incriminated obesity and diabetes as contributors in the occurrence of severe COVID-19 outcomes such as intensive care unit admissions and deaths [ 8 ]. However, studies that explored the association between COVID-19 severe outcomes (disease case fatality or disability-adjusted life years, DALYs) at regional level and/or air pollution are scarcely found in the medical literature.…”
Section: Introductionmentioning
confidence: 99%
“…For the outcome that exhibited a significant correlation with exposure in TSMR, we performed another TSMR for another independent GWAS. Then, meta-analysis across different GWAS cohorts was performed using fixed-effects analysis, under the assumption that 1 true effect size applied across all GWAS considered, as in previous studies[ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, genic IVs can be identified by searching through databases or reports that assess the relationship between genetic factors and the observed variable in question. Previous genome-wide association studies (GWASs) are especially useful in this regard [ 146 , 147 ], as they are hypothesis-free scans that depict the correlation between millions of SNPs and the observed variables and clinical outcomes.…”
Section: Evaluating the Consequences Of Controlling Confounders On Th...mentioning
confidence: 99%